Analysing dynamics and synthesising a robust vector control for the dc‐voltage power port based on the modular multilevel converter in multi‐infeed AC/DC smart grids. Issue 4 (13th September 2019) - Davari, Masoud; Gao, Weinan; Blaabjerg, Frede
Abstract : Among all converters, one of the most prominent technologies employed in multi‐infeed ac/dc (MIACDC) smart grids is the modular multilevel converters (MMCs). The core part of the MIACDC grids is their dc‐voltage power port. All MMC's components in a dc‐voltage power port – which are capable of significantly impacting on the dynamics – are mathematically modelled in the space‐phasor representation using the rotating dq ‐frame. Afterwards, the effects of each submodule capacitors and arm inductors on the dc‐voltage power port's dynamics are investigated and analysed, separately. This paper mathematically shows that the former is affecting the low‐frequency range of the bandwidth, and the latter is impacting on the high‐frequency one. Moreover, this paper demonstrates that a robust, optimal controller synthesized by the µ ‐analysis is a good candidate to induce both robust stability and performance in an MMC‐based dc‐voltage power port. In order to illustrate the contributions of this article, detailed mathematical analyses; comparative results simulated by the switching model of MMC; and experimental results produced by a test rig, which is able to examine the transient performance of an MMC‐based dc‐voltage power port, are provided. For comparison, the results of the PI‐Lead controller and those of another controller optimally synthesized have been provided.